Désaffection pour les études scientifiques et recherche en éducation scientifique - JEAN-MARIE BOILEVIN (Metaichmio Publications, 2014)
To face the phenomenon of disaffection for scientific studies, many reports have been published in France and internationally. But educational research has also studied the issue. This paper presents a content analysis of these reports and some of the research on the subject. A summary of findings, reasons given and the recommendations made in the fight against the phenomenon of disaffection for scientific studies is available. It identifies possible areas of research in science education. This analysis is also an opportunity to question the links between science education and research policy makers and institutions but also to discuss the objectives and purposes of science education, few topics in depth all the reports available.